LUCICAT Model as a river flow forecasting tool: an experiment with Fitzroy River catchment of Western Australia - Islam, S.A.; Anwar, Faisal; Ezzy, G.; Bari, M. (The Modelling and Simulation Society of Australia and New Zealand Inc, 2013)
Early warnings of river flow, particularly high flow, allow individuals, communities and industries to respond in an appropriate manner to reduce the probability of suffering, personal injury, death and economic loss. To increase the lead time of river forecasting, major river forecasting centers across the world are using numerical weather predictions for continuous river flow forecasting. Low flow forecasting is also important to many stakeholders like water resources managers and farmers. The Land Use Change Incorporated Catchment (LUCICAT) model is a distributed lumped conceptual model which is widely used for water resources assessment in most of the Western Australian catchments and few eastern state catchments. This study aims at investigating LUCICAT model’s potential in continuous river flow forecasting. The experiment is carried out in Fitzroy River catchment of Western Australia for simulating both high and low flow in hourly time step with an emphasis towards high flow. The model consists of two components: (a) the daily Water Balance Model (WBM) and (b) the Flood module. The daily WBM was calibrated for the period of 1961-2010 using observed daily stream flow data at 11 gauging stations against a set of calibration criteria which were (i) joint plot of observed and simulated daily flow series, (ii) scatter plot of monthly and annual flow, (iii) flow-period Error Index, (iv) Nash-Sutcliffe Efficiency, (v) Explained variance, (vi) Correlation Coefficient, (vii) overall water balance and (viii) flow duration curves.The Flood module was calibrated for 2006 flow event using observed hourly discharge and stage height data. The Flood module takes catchment initial condition from the daily WBM at a particular date from which the Flood module start running in hourly time step. For calibrating the Flood module, calibrated set of parameter from the daily WBM were taken and three parameters were adjusted which were (i) Dry water store soil moisture exponent, (ii) Wet water store soil moisture exponent and (iii) Lateral conductivity wet store (mm/day). Six separate flow events have been simulated in hourly time step to test following three hypotheses: (i) a single set of parameters is valid for the whole catchment, (ii) a single set of parameters is valid for different flood events, and (iii) no change of parameter is required during operational prediction. Findings suggest that the hypotheses are valid and the model has fairly good potential in simulating continuous river flow, both high and low flow. Hence, once the model is calibrated for a particular catchment, it can be used for water resources assessment and continuous river flow forecasting.